Premises and Problems : Essays on World Literature and Cinema - Moreira, Luiza Franco; Moreira, Luiza Franco (Book collections on Project MUSE., 2021)
"Discusses world literature and cinema from the perspective of literary languages and film traditions that do not hold a hegemonic position"--